2018
DOI: 10.3168/jds.2017-13133
|View full text |Cite
|
Sign up to set email alerts
|

Mild and severe udder cleft dermatitis—Prevalence and risk factors in Swedish dairy herds

Abstract: Udder cleft dermatitis (UCD) is an inflammatory skin condition affecting the anterior parts of the udder of dairy cows. The lesions may present as mild or severe skin lesions and have been associated with mastitis and digital dermatitis. The full etiology and pathogenesis are not understood and no large-scale studies have investigated prevalence and risk factors. Therefore, the main objectives of the study were to investigate the prevalence of mild and severe UCD in Swedish dairy herds and to identify risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(64 citation statements)
references
References 14 publications
5
57
2
Order By: Relevance
“…In recent work, Schmidt and coauthors did not identify eta, etb, or etd in bovine isolates, and they reported that only one human S. aureus isolate tested positive for eta (4). It is possible that our finding in the current study may be a result of the coincidence of mastitis with different dermatitis conditions, for example, hock lesions (39) or udder cleft dermatitis (40,41). Udder cleft dermatitis is a pathology lacking a clear etiology, but one of the bacterial inducers can be S. aureus.…”
Section: Discussionmentioning
confidence: 88%
“…In recent work, Schmidt and coauthors did not identify eta, etb, or etd in bovine isolates, and they reported that only one human S. aureus isolate tested positive for eta (4). It is possible that our finding in the current study may be a result of the coincidence of mastitis with different dermatitis conditions, for example, hock lesions (39) or udder cleft dermatitis (40,41). Udder cleft dermatitis is a pathology lacking a clear etiology, but one of the bacterial inducers can be S. aureus.…”
Section: Discussionmentioning
confidence: 88%
“…Herd selection and data collection were performed as described in Ekman et al [ 24 ]. Briefly, 100 randomly selected Swedish dairy herds with freestall housing, herd size of 50–210 cows, and affiliation with the Swedish Official Milk Recording Scheme (SOMRS) were enrolled in a cross-sectional study.…”
Section: Methodsmentioning
confidence: 99%
“…The US National Animal Health Monitoring System stated that digital dermatitis (DD) is the second most common health concern in dairy cattle (USDA, 2009). Digital dermatitis was first reported in Italy by Cheli and Mortellaro (1974) and described subsequently in many countries worldwide (Laven, 2001; Demirkan and Güzel, 2004;Holzhauer et al, 2006;Cartwright, et al, 2017;Ekman, et al, 2018). This disease causes significant financial loss and lowered welfare in affected cattle (Winckler and Willen, 2001); the severe pain caused by lesions is sufficient to reduce milk yield (Nielsen et al, 2012), estimated at around $190 ± 30 million annually in the US dairy industry (Losinger, 2006).…”
Section: Introductionmentioning
confidence: 99%